Microencapsulated islet-like microtissues with toroid geometry for enhanced cellular viability - Chen, Yang (2022)
Transplantation of immuno-isolated islets is a promising strategy to restore insulin-secreting function in patients with Type 1 diabetes. However, the clinical translation of this treatment approach remains elusive due to the loss of islet viability resulting from hypoxia at the avascular transplantation site. To address this challenge, we designed non-spherical islet-like microtissues and investigated the effect of their geometries on cellular viability. Insulinsecreting microtissues with different shapes were fabricated by assembly of monodispersed rat insulinoma beta cells on micromolded nonadhesive hydrogels. Our study quantitatively demonstrated that toroid microtissues exhibited enhanced cellular viability and metabolic activity compared to rod and spheroid microtissues with the same volume. At a similar level of cellular viability, toroid geometry facilitated efficient packing of more cells into each microtissue than rod and spheroid geometries. In addition, toroid microtissues maintained the characteristic glucose-responsive insulin secretion of rat-derived beta cells. Furthermore, toroid microtissues preserved their geometry and structural integrity following their microencapsulation in immuno-isolatory alginate hydrogel. Our study suggests that adopting toroid geometry in designing therapeutic microtissues potentially reduces mass loss of cellular grafts and thereby may improve the performance of transplanted islets towards a clinically viable cure for Type 1 diabetes.